Factors that Boost and Hinder the Transition from Traditional to Self-managed Teams: A Systematic Literature Review - Lima, Rayfran Rocha; Costa, Marcelo Santana; Oran, Ana Carolina; França, César (Anais do Simpósio Brasileiro de Qualidade de Software (SBQS), 2022)
Background: Considering the required speed of organizational transitions to keep software development competitive, transitions based on a trial-and-error approach are less and less acceptable. Even so, due to the lack of a systematic process and knowledge capable of guiding the transition of traditional teams to self-managed teams (SMT) companies have faced difficulties in completing this mission, becoming dependent on individual efforts with unpredictable results. Objective: This work aims to analyze available scientific publications in order to characterize the critical factors related to the transition from traditional teams to SMT in a software development context. Method: We used the Scopus scientific database to conduct a Systematic Literature Review on its available publications in the last 5 years. Results: A total of 14 factors capable of boosting or hindering the team transition toward SMT were labeled into 6 interdependent perspectives through analysis of the evidence provided by 28 selected publications. Conclusion: Our findings show that this transition cannot be seen as an isolated process with immediate results and that there is still much to investigate about the transition of traditional teams to SMT in the software development industry.